Digital Marketing Strategy Training for Micro and Small Business Actors in Bagan Percut - Mohammad Syarif Sumantri; Amril; Lambok Manurung (Outline Publisher, 2023)
Digital Marketing Strategy Training for Micro and Small Business Actors in Bagan Percut aims to improve digital literacy and marketing skills of MSME actors in utilizing technology to expand market reach and increase business competitiveness. This activity involved 30 business actors from various sectors, such as culinary, handicrafts, and services. The results of the training showed an increase in participants' digital literacy, ability to produce more attractive promotional content, and success in expanding market reach. As many as 60% of participants reported increased interaction on their business's social media, while 50% succeeded in getting new customers. The results of this training show that digital marketing strategies can be an effective solution for MSME actors in facing challenges in the digital era, while contributing to local economic development.